The Four Divine Presences in al-Jīlānī’s (470/1077-561/1165) Thoughts - Waryani Fajar Riyanto (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Absence of God (al-ghiyāb al-ilāhiyya) in Western cosmology has fostered a mechanistic understanding of the universe as operating independently. In contrast, Islamic cosmology, particularly in the Sufi tradition, emphasizes the continuous and holistic presence of God (al-ḥaḍrah al-ilāhiyya). This study explores the cosmological thought of Shaykh ‘Abd al-Qādir al-Jīlānī (470/1077–561/1165), founder of the Qādiriyya Ṣūfī order. Employing a qualitative library research approach, the study analyzes al-Jīlānī’s Sirr al-Asrār (The Secret of Secrets) alongside other relevant works using an Islamic cosmic levels-cycles framework and expert triangulation of Sufi thought. The findings reveal that al-Jīlānī’s divine cosmology presents an integrated vision linking four divine presences (al-ḥaḍarāt al-ilāhiyya al-arba‘ah): lāhūt (Godhead), jabarūt (Divine Power), malakūt (Spiritual Sovereignty), and nāsūt (Humanity). These four levels are systematically correlated with eight cosmological elements, including the apostles, cosmos, spiritual centers, heavens, spirits, knowledge, existential levels, and human intellect. Al-Jīlānī’s holistic model offers an integrative alternative to mechanistic cosmology and reinforces the spiritual unity of God, humanity, and the universe. Contribution: The findings in this study contribute to reinforcing the concept of integralism in cosmic spirituality, wisdom of cosmology, sacred cosmology, spiritual-holistic cosmology, and mechanistic cosmology.